Corporate management, systems paradigm, ethics : a philosophical-ethical investigation into the implications of the ethical values of the systems paradigm for corporate environmental management in developing countries - Voges, Frederik Wilhelm Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1995.